An integrative action reserch for recruitment and developing leadership skills of C3 church's youth ministry - Phyu, Moe Pwint (Animo Repository, 2016)
This study focused on the developing leaders of the youth ministry in Christian City Church Makati (C3 Church Makati). The youth ministry was formed for youths spiritual formation, growth and youth are encouraged to involve in the church community by participating church activities such as the children ministry, music ministry, church outreach programs, evangelism, feeding, and hygiene programs to street kids. When student leaders could not perform well in their expected roles, there was less participation of the youth members in the ministry. This was found to be the main issue of the Church. To address the issue, I have undertaken an action research on recruitment of new youth leadership team. During the action research, the first intervention focused on the selection of new members of the leadership team. The second intervention focused on the youths leadership skills development with spiritual empowerment. The high impact model of volunteer ministry development was used for the first intervention and Connexions 5Cs model was used for the second intervention. Selected new leaders formed their respective ministry area teams and developed organized approach of leading their members after the first intervention. Manifestation of leadership skills of student leaders and improvement of the entire youth group with an increased number of participation of youth members in the church activities were seen as the research success indicators after the second intervention.